When Sports Conquered the Republic: A Forgotten Chapter From the «Roaring Twenties.» - Wolfgang Rothe (Studies in 20th & 21st Century Literature, 1979)
After the First World War, sport experienced an astonishing growth in the successor states to the two empires of central Europe, a growth which can only be explained sociologically in terms of the general character of the twentieth century as a «physical century.» Furthermore, the intellectual climate of the times as well as the psychic state of the freshly-hatched Republicans plays a special role. That is, the enormous fascination with the «Moloch of sport» can be explained on the one hand by a non-intellectual worshipping of purely physical, measurable maximum achievements (record-mania), on the other by the America-cult that arose during this period (identical with the positive myth of technology, the cult of machines that replaced the pre-war view). A third factor was the cult of heroes, the need to worship «great men» that was not extinguished in 1918 and which had only sought new objects. The top sportsman was one of these new objects of identification. In astonishing (and hard to explain) contradiction to the exorbitant value placed on sport in the life of the twenties, the number of distinctive literary works on sport is relatively small—much smaller than in the post-1945 period. These reflect the prevailing enthusiasm for sport, sometimes naively and positively, sometimes negatively and ironically. An expansion of the sport theme into a true philosophy of life occurs in the only sport-novel of the twenties, Kasimir Edschmid's Sport um Gagaly, which to some degree continues the traditional German Bildungsroman, but does so in a hopelessly elitist and snobbish way.
Keywords: First World War; central Europe; twentieth century; physical century; Republican; record-mania; America-cult; Kasimir Edschmid; Sport um Gagaly; Bildungsroman; German; tradition